The Significance of Shakespeare in Gabriel Josipovici's Work. Issue 1 (1st March 2019) - Gunn, Dan
Abstract : The present article seeks to analyse the place of Shakespeare's work within the oeuvre of Gabriel Josipovici, starting with the latter's first published critical book, The World and the Book, and ending with his most recent, Hamlet: Fold on Fold. In the early work Josipovici sought to establish a direct line between the Middle Ages and Modernism, yet Shakespeare was already a presence whose plays obliged that line to deviate. In his later critical work, such as On Trust, Shakespeare becomes one of the figures who allows Josipovici to exemplify clearly the crucial gap he wishes to explore between saying and doing. This gap is most fully explored in the recent book on Hamlet, where the protagonist is seen as the supreme literary example of what happens when the traditions governing doing have fallen away, leaving the character adrift in a sea of possibilities of utterance and action, none of which has the feel of necessity.